Natural resources and wealth inequality: A cross-country analysis - Sosson Tadadjeu; Henri Njangang Ndieupa; Simplice Asongu; Yann Nounamo (African Governance and Development Institute (AGDI), 2021)
This study investigates the impact of natural resources on wealth inequality as a first attempt on a panel of 45 developed and developing countries over the period 2000-2014. Using the Generalized Method of Moments, the results provide stong evidence that natural resources increase wealth inequality within a linear empirical framework. These results are robust to the use of alternative natural resources and wealth inequality measures. Additionnaly, a nonlinear analysis provides evidence of an inverted U shaped relationship between natural resources and wealth inequality. The net effect of enhancing natural resources on wealth inequality is positive and building on the corresponding conditional negative effect, the attendant natural resource thresholds for inclusive development are provided. It follows that while natural resources increase wealth inequality, some critical levels of natural resources are needed for natural resources to reduce wealth inequality.
Keywords: F21; F54; L71; 330; Oil wealth; Natural resources; Wealth inequality; Sustainable development